Molecular Mechanisms of Intercellular Rhizobial Infection: Novel Findings of an Ancient Process - Quilbé, Johan; Montiel, Jesús; Arrighi, Jean-François; Stougaard, Jens (Frontiers in Plant Science, 2022)
Establishment of the root-nodule symbiosis in legumes involves rhizobial infection of nodule primordia in the root cortex that is dependent on rhizobia crossing the root epidermal barrier. Two mechanisms have been described: either through root hair infection threads or through the intercellular passage of bacteria. Among the legume genera investigated, around 75% use root hair entry and around 25% the intercellular entry mode. Root-hair infection thread-mediated infection has been extensively studied in the model legumes Medicago truncatula and Lotus japonicus. In contrast, the molecular circuit recruited during intercellular infection, which is presumably an ancient and simpler pathway, remains poorly known. In recent years, important discoveries have been made to better understand the transcriptome response and the genetic components involved in legumes with obligate (Aeschynomene and Arachis spp.) and conditional (Lotus and Sesbania spp.) intercellular rhizobial infections. This review addresses these novel findings and briefly considers possible future research to shed light on the molecular players that orchestrate intercellular infection in legumes.